2008
DOI: 10.1213/ane.0b013e31817bd143
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrest After Spinal Anesthesia in Thailand: A Prospective Multicenter Registry of 40,271 Anesthetics

Abstract: The incidence of cardiac arrest during spinal anesthesia was infrequent, but was associated with a high mortality rate. If the surgeon performed the spinal anesthetic, this was a significant factor associated with cardiac arrest. Increasing the number of anesthesiologists, improving monitoring guidelines for spinal anesthesia and improving the nurse-anesthetist training program may decrease the frequency of arrest and/or improve patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 17 publications
1
26
0
1
Order By: Relevance
“…Two major groups of patients having cardiac arrest during spinal anesthesia were patients undergoing cesarean delivery and surgery to the lower extremity. [9] Such a large bone fractures in case of relatively emergency traumatology of patients of ASA classification status be left partially in the background is the long-term quality of life ahead. Neuraxial block in our case was chosen because of advanced age, obesity and overall physical condition was to be fond of.…”
Section: Discussionmentioning
confidence: 99%
“…Two major groups of patients having cardiac arrest during spinal anesthesia were patients undergoing cesarean delivery and surgery to the lower extremity. [9] Such a large bone fractures in case of relatively emergency traumatology of patients of ASA classification status be left partially in the background is the long-term quality of life ahead. Neuraxial block in our case was chosen because of advanced age, obesity and overall physical condition was to be fond of.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was one case of maternal mortality, which was reported as part of a multicenter registry of patients receiving spinal anesthesia in Thailand [7]. The case was in a 33 y-old parturient, scheduled for elective cesarean delivery.…”
Section: Anesthesia For Cesarean Section In Placenta Previamentioning
confidence: 99%
“…Induction of general anesthesia was performed during the hysterectomy. Maternal fatality occurred after massive hemorrhage with disseminated intravascular coagulopathy and a ruptured bladder [7].…”
Section: Anesthesia For Cesarean Section In Placenta Previamentioning
confidence: 99%
“…Koop et al 5 and liguori et al 19 observed that, in several episodes of documented cA, recordings immediately before and after the event did not indicate cases of arterial oxygen saturation below 90%. Besides, those authors demonstrated that many patients who developed cA had not received sedative drugs 3,10,19,20 .…”
Section: Introductionmentioning
confidence: 98%
“…to determine the frequency of cardiac arrest during spinal anesthesia, investigators observed a remarkably heterogenous incidence, ranging from 1.3 to 18 cases in 10,000 spinal anesthesias 5,[8][9][10] .…”
Section: Introductionmentioning
confidence: 99%